1. 1-sin x + 1-cos x = sin x + cos x-1
cos x sin x sin x cos x
2. sec^2x - tan^2 x + tan x = sin x + cos x
sec x
3. sin^3 x - sin x + cos x = cot x - cos^2 x
sin x
4. 1 + cot A + sec A _ tan A = sin A + cos A
csc A
1. 1-sin x + 1-cos x = sin x + cos x-1
cos x sin x sin x cos x
2. sec^2x - tan^2 x + tan x = sin x + cos x
sec x
3. sin^3 x - sin x + cos x = cot x - cos^2 x
sin x
4. 1 + cot A + sec A _ tan A = sin A + cos A
csc A
Hint: Multiply both sides of the equation by sin(x) cos(x) and then try it.
Convert everything to sines and cosines:
Now add the fractions.
What's ? Hint: It's a familiar identity that has been slightly rewritten.
Convert everything to sines and cosines and simplify:
-Dan